The Best of Both Worlds. Issue 2 (September 2016) - Bienert, Hans‐Dieter
Abstract: In an enthusiastically received exhibition, the Metropolitan Museum of Art together with the National Museums in Berlin and other leading research museums presented the treasures of the Hellenistic world in New York. The DFG was also involved as the funding body of numerous excavation projects and co‐organiser of an accompanying symposium.